Retrospective Study of Fishery Interactions in Stranded Cetaceans, Canary Islands - Puig-Lozano, Raquel; Fernández, Antonio; Sierra, Eva; Saavedra, Pedro; Suárez-Santana, Cristian M.; De la Fuente, Jesús; Díaz-Delgado, Josué; Godinho, Ana; García-Álvarez, Natalia; Zucca, Daniele; Xuriach, Aina; Arregui, Marina; et al. (Frontiers in Veterinary Science, 2020)
Estimating cetacean interactions with fishery activities is challenging. Bycatch and chronic entanglements are responsible for thousands of cetacean deaths per year globally. This study represents the first systematic approach to the postmortem investigation of fishery interactions in stranded cetaceans in the Canary Islands. We retrospectively studied 586 cases necropsied between January 2000 and December 2018. Of the cases with a known cause of death, 7.4% (32/453) were due to fishery interactions, and the Atlantic spotted dolphin (Stenella frontalis) was the most affected species [46.9% (15/32)]. Three types of fishery interactions were recognized by gross findings: bycatch [65.6% (21/32)], chronic entanglements [18.8% (6/32)], and fishermen aggression [15.6% (5/32)]. Among the bycaught cases, we differentiated the dolphins that died because of ingestion of longline hooks [23.8% (5/21)] from those that died because of fishing net entrapments [76.2% (16/21)], including dolphins that presumably died at depth due to peracute underwater entrapment (PUE) [37.5% (6/16)], dolphins that were hauled out alive and suffered additional trauma during handling [43.8% (7/16)], and those that were released alive but became stranded and died because of fishery interactions [18.7% (3/16)]. Gross and histologic findings of animals in each group were presented and compared. The histological approach confirmed gross lesions and excluded other possible causes of death. Cetaceans in good-fair body condition and shallow diving species were significantly more affected by fishery interactions, in agreement with the literature. Low rates of fishery interactions have been described, compared with other regions. However, within the last few years, sightings of entangled live whales, especially the minke whale (Balaenoptera acutorostrata) and Bryde’s whale (B. edeni), have increased. This study contributes to further improvement of the evaluation of different types of fishery interactions and may facilitate the enforcement of future conservation policies to preserve cetacean populations in the Canary Islands.